Grain yield and yield components of commercial ZP maize hybrids from different maturity groups - Čamdžija Zoran; Filipović Milomir; Stevanović Milan; Mladenović-Drinić Snežana; Vančetović Jelena; Babić Milosav (Selekcija i Semenarstvo, 2012)
Maize breeding program in the Maize Research Institute 'Zemun Polje' is continuously working to create hybrids with higher genetic potential and greater adaptability. New hybrids ZP 505, ZP 555, ZP 560, ZP 600 and ZP 606 are hybrids of the last cycle of selection and they are characterized by a higher genetic potential and stability. Hybrids of early medium maturity group, ZP 341, ZP 362, ZP 427 and ZP 434 are recommended for planting in less favorable growing conditions, as data of stability parameters show values less than 1 (0.88-0.95), and hybrids of later maturity groups FAO 600-700 are more recommended for more favorable growing conditions, because they show values above 1 by Eberhart and Russell. Hybrids of maturity group FAO 500 are characterized by high yields and excellent stability (0.99 to 1.06). Correlation coefficient showed a significant correlation between yield and ear length, and between yield and number of kernel rows. .